Lamotrigine Novel Cocrystals: An Attempt To Enhance Physicochemical Parameters (Journal of Pharmaceutical Negative Results, 2022)
Background: Cocrystals are defined as multiple component structures whose components interact through non-covalent interactions.Cocrystals can enhance other essential properties of the APIs.Aim: The current research work focuses on formulating and evaluating novel co-crystals of Lamotrigine anti-epileptic drug (BCS-II)Methods: The Cocrystals of Lamotrigine drug with different cocrystals formers like Saccharin sodium, 4-Hydroxy benzoic acid, andMethyl paraben used with molar ratios (1:1) were prepared by solvent drop method, co-grinding method, and solvent evaporationmethod.Results: The results signify the establishment of intermolecular interaction within the cocrystals. In the novel cocrystals, Lamotriginewas determined to be engaged in the hydrogen bond interaction with the complementary functional groups of Saccharin sodium, 4-Hydroxy benzoic acid, and methyl paraben. Compared with the pure Lamotrigine flow properties for prepared co-crystal by usingsolvent evaporation method crystals are showing excellent flow properties. LTG-SAC CF I, LTG-HBA I, and LTG-MP III showed49.6 folds, 7.4 folds, and 3.36 folds improved solubility respectively. The dissolution test showed that the LTG-SAC CF I, LTG-HBAI, and LTG-MP III cocrystals exhibited a 1.09-fold, 1.08-fold, and 1.07-fold higher dissolution rate than the pure Lamotrigine.Conclusions: LTG-SAC CF I, LTG-HBA I, and LTG-MP III cocrystals showed modification in the chemical environment,intermolecular interactions were established, improved flow properties with enhanced intrinsic solubility and in-vitro dissolution ratethan pure drug.